ORAL HEALTH STATUS OF 9 TO 12 YEAR OLD SCHOOL GOING CHILDREN IN URBAN MEERUT - Sharma, Saurabh; Parashar, P; Srivastava, A; Bansal, Rahul (Indian Journal of Community Health, 2013)
Background: Oral health is an integral part of general health. Oral Health status has a direct impact on general health and conversely, general health influences oral health. It has also become clear that causative and risk factors in oral diseases are often the same as those implicated in the major general diseases.Hence this study was done to estimate the prevalence, type and degree of oral diseases in the study area. Materials and Method: It is a cross- sectional study design conducted among schools in , Multan Nagar which is the field practice area of department of Community Medicine, SMC (Subharti Medical College), Meerut.A total of 534 school going children aged 9 to 12 years old were examined using standard WHO Oral Health Survey methods. Results: One third of the study population (34.3%) had good oral hygiene according to oral hygiene index simplified. The overall prevalence of gingivitis among children was 53.4 percent.The prevalence of dental caries among 9 to 12 year old school going children was 60.1 %. The mean DMFT score of the study population was 0.89.The index study findings revealed a strong relationship between oral health status and socio economic status and mother’s educational status. Conclusion: The overall prevalence of dental caries was high in the study subjects.Mother’s educational status has a significant role in improving the oral health status of children.